Application of constructivism learning in guided essay writing - Othman, A.J.; Norzan, N.; Abdul Samad, R.S.; Darusalam, G.; Sharatol, S. (2012)
Constructivism is based on the premise that learners actively construct their own learning. this article explores the use of constructivism in guided essay writing. it compares the traditional method of teaching guided writing with the constructivist approach. the changing roles of students and teachers under the constructivism are discussed.